An ionic coordination hybrid hydrogel for bioseparation. Issue 43 (15th May 2017) - Liu, Zhen; Xia, Zhijun; Fan, Liuyin; Xiao, Hua; Cao, Chengxi
Abstract : An ionic coordination hybrid hydrogel is formed with ionic and covalent crosslinked networks via one-step copolymation. Abstract : An ionic coordination hybrid hydrogel is formed with ionic and covalent crosslinked networks via one-step copolymation. It is demonstrated that the hybrid crosslinker gel is used as a separation matrix for bioseparation, showing high separation efficiency, in contrast to traditional polyacrylamide gels. The hydrogel might serve as a novel matrix for bioseparation.